AFMA Hardware Sdn. Bhd. / Nor Azam Ahmad … [et al.] - Ahmad, Nor Azam; Ismail, Noraszaini; Zulkepli, Mazli; Mamat, Mohamad Faizal (2000)
A world of entrepreneurships and business is a field of economic that returns profit. But it needs patience and concentration. Prophet Muhammad said ‘9 over 10 our rezeki come from business. For this reason, we take an initiative to involve in business as a supplier and seller hardware. Business actually needs bravery and commitment in facing any barriers or problem. Besides that, it also needs high spirit, creativity and able to seek any chances that involve in new era at business. So that Bumiputra need preparation from aspect physical mental and spiritual. Industrial development in Malaysia has growing up and that why Malaysia has turn from small industry to big industry. High demand in this industry has become a focus by producer. So, we agreed to establish a partnership business called AFMA Hardware Sdn. Bhd. that act as intermediaries between supplier and customer. We hope that the establishment of our company becomes a prentice to all other Bumiputra to involve in this business.